Effective communication with difficult to reach landholders. Issue 2 (3rd April 2017) - Morrison, Mark; Greig, Jenni; Waller, David; McCulloch, Roderick; Read, Donna
ABSTRACT: While considerable research has been undertaken to understand which communication channels are most effective at reaching landholders, much less research has examined which communication channels are most effective for reaching those landholder segments characterised by low program participation (i.e. 'lifestylers', traditional and absentee segments). Even less research has examined what messages most effectively engage these landholders, or landholders in general. In this study, eight communications campaigns were developed with specific messages and appeals that allowed us to examine the perceptions of difficult-to-reach landholders towards rational versus emotional, inform versus persuade and individual versus community-based appeals, using a qualitative methodology. The findings indicate that landholder's perceptions of both rational and emotional messages depended on the congruence with segment values. Inform messages were found often to be well regarded, especially when they clarified eligibility and program benefits. Persuade messages could be effective, but this also depended on the consistency of the message with segment values. Community-based messages were often not well received, but they could be effective at reaching lifestylers.